Efficacy of the cardiac glycoside digoxin as an adjunct to csDMARDs in rheumatoid arthritis patients: a randomized, double-blind, placebo-controlled trial - El-Mahdy, Nageh A.; Tadros, Mariam G.; El-Masry, Thanaa A.; Binsaleh, Ammena Y.; Alsubaie, Nawal; Alrossies, Amani; Abd Elhamid, Medhat I.; Osman, Enas Y.; Shalaby, Hadeel M.; Saif, Dalia S. (Frontiers in Pharmacology, 2024)
Background: Inflammation and angiogenesis are two main mechanisms that act as mutual pathways in rheumatoid arthritis (RA). This work aimed to study the efficacy of digoxin as an adjunct therapy to conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs) in active RA patients. Methods: In a randomized, double-blinded, placebo-controlled study, 60 adult patients with active RA received a placebo or digoxin (0.25 mg every other day) combined with csDMARDs for six months. The American College of Rheumatology (ACR) 20, ACR50, and ACR70 response rates and the disease activity score (DAS28) were assessed for patients. Flow cytometric analysis of Th17 cells and serum concentrations of IL-17A, IL-23, HIF-1α, and VEGF were evaluated before and after three and six months of therapy. Results: Following three and six months of digoxin therapy combined with csDMARDs, significant differences were detected in laboratory and clinical parameters relative to the control group. After six months, 83.3% of patients in the digoxin group, compared to 56.7% in the control group, achieved an ACR20 response (p = 0.024). The digoxin group had a significantly higher percentage of patients who achieved DAS28 remission after six months (p = 0.024). Notable improvements in the Health Assessment Questionnaire Disability Index, ACR50, and ACR70 were detected in the digoxin group. Conclusion: Digoxin was well tolerated and exerted profound immunomodulatory and anti-inflammatory effects in RA patients, and may also exhibit anti-angiogenic properties, indicating that it might be an effective adjunct to csDMARDs in treating RA.